The IRB, the HSR – and the Ethics of Insider Research - Jane Zeni (Networks: An Online Journal for Teacher Research, 2001)
This project began about eight years ago when I tried adapt the mandated "human subjects review" (HSR) by my university's Institutional Review Board (IRB) to the work I was doing as a researcher of my own practice and as a consultant to K-12 teacher researchers. After many roadblocks and revisions, I produced a guide intended, not for IRB review, but for discussion in action research groups and dissertation committees. It was first published in Educational Action Research (1998, vol 6, no. 1), then revised and updated as the Epilogue to the new book (Zeni, 2001). Despite its convoluted genealogy, the Guide and its heuristic questions have proven useful to researchers trying to make ethical decisions amid the alphabet soup of regulations. Today I believe we must engage in dialogue about ethics with two very different groups. We must talk with the traditional arbiters of research ethics – the Institutional Review Boards that control access to research funding and academic degrees. However, we cannot allow this dialogue to stay within the walls of the universities; we must widen the conversation to include the stakeholders in the schools where most practitioner research is conducted.